Third-Order Quadrature Oscillator Circuit with Current and Voltage Outputs. (3rd October 2013) - Chaturvedi, Bhartendu; Maheshwari, Sudhanshu
Abstract : The paper presents a new quadrature oscillator of third order which can provide four quadrature current outputs and two quadrature voltage outputs. The new circuit employs three differential voltage current conveyors and six passive components, most of which are in grounded form. Circuit operation at high frequencies is verified along with nonideality and parasitic study. The circuit enhancement for generation of four phase clock waveforms is also given. The proposed circuit is a novel addition to the oscillator family.